2019
DOI: 10.1038/s41419-019-2028-9
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ0005276 promotes the proliferation and migration of prostate cancer cells by interacting with FUS to transcriptionally activate XIAP

Abstract: Prostate cancer (PCa) is one of the major men’s malignancies with high mortality worldwide. Circular RNAs (circRNAs) have been shown to serve as essential regulators in human cancers. CircRNA can exert their functions by cooperating with their host genes. In the present study, microarray analysis revealed an upregulated mRNA in PCa samples. X-linked inhibitor of apoptosis protein (XIAP), a key regulator in the progression of human cancers. Through bioinformatics analysis, we determined that XIAP is a host gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 42 publications
(41 reference statements)
1
91
0
Order By: Relevance
“…In our current study, we determined that LINC01106 recruited FUS to Gli1 and Gli2 promoters, thereby strengthening the expression of Gli1 and Gli2. Finally, we also proved the partial reversing effect of Gli1 and Gli2 on LINC01106-mediated CRC cell functions 47 . More importantly, co-overexpression of Gli1, Gli2, and Gli4 totally reversed the effect of silenced LINC01106 on CRC progression.…”
Section: Discussionmentioning
confidence: 56%
“…In our current study, we determined that LINC01106 recruited FUS to Gli1 and Gli2 promoters, thereby strengthening the expression of Gli1 and Gli2. Finally, we also proved the partial reversing effect of Gli1 and Gli2 on LINC01106-mediated CRC cell functions 47 . More importantly, co-overexpression of Gli1, Gli2, and Gli4 totally reversed the effect of silenced LINC01106 on CRC progression.…”
Section: Discussionmentioning
confidence: 56%
“…For example, circRNA circ0005276 interacted with FUS binding protein (FUS) so as to activate the transcription of XIAP. Rescue assays were conducted to determine the crucial role of XIAP in circ0005276 and FUS-mediated PCa cellular processes 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the advent of high-throughput sequencing associated with new computational pipelines to map circRNAs to the genome have moved circRNAs to the forefront of RNA research [16,17]. Emerging evidence showed that circRNAs exhibited aberrant expression and played critical roles in many types of cancer, including prostate cancer [18][19][20][21]. Recently, studies reported that circANKS1B was overexpressed and involved in tumorous progression in breast cancer [12] and colorectal cancer [13], respectively.…”
Section: Discussionmentioning
confidence: 99%